Competitive supply chain resilience: gaining competitive advantage through innovation & collaboration - Wilding, Richard (Henry Stewart Talks, 2010)
Innovative methods for improving supply chain process, systems and structure, Maintaining your competitive advantage in a changing environment, Competitive Supply Chain Resilience: methods to gain advantage, The new supply chain skill set: the qualifiers and winners